Impact of Free-range Poultry Production Systems on Animal Health, Human Health, Productivity, Environment, Food Safety, and Animal Welfare Issues - Jacob, Jacqueline P.; Pescatore, Anthony J.; Anderson, Kenneth E.; McCrea, Brigid; Shaw, Daniel P. (Council for Agricultural Science and Technology (CAST), 2018)
As farmers in the United States try to develop new poultry operations, there are two main possibilities. The first is to work within the existing vertically integrated systems. The second is to develop independent, smaller operations. Those that choose the second option look toward alternative production systems, such as free-range poultry production. As such, these individuals often find that there is a distinct lack of usable definitions and knowledge, as well as a great deal of confounding research related to this field. The popularity and beliefs associated with what some consider a return to old systems are very strong and have not dissipated. The consumer has worked to fuel this movement toward free-range, organic, or even simply what some consider natural poultry production.This publication serves to review what is known about poultry egg and meat production with specific attention to available research on free-range production systems. Stressors related to alternatively housed and managed birds, as well as the known advantages anddisadvantages for farmers, are reviewed. Food quality and food safety in regard to poultry meat and eggs are often understood by farmers and consumers as oneand the same. Clarification of food quality and food safety with regard to poultry production systems will be discussed. The role of farming systems in disease control is included in this discussion.Attention to the environmental system, soil contamination, and manure burdens placed on the land by free-range poultry is also considered. This consolidation ofinformation is aimed at helping further the discussion of free-range poultry as it pertains to larger farming systems and the future of this growing field of niche market poultry production.
Keywords: Free-Range; Animal Welfare; Food Safety